Adsorptive Desulfurization of Iraqi Light Naphtha Using Calcite and Modified Calcite - Qasim, Ahmed; Alwan, Hameed Hussein (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
This study used the adsorption method to remove sulfur compounds from light naphtha fuel by using calcite and modified calcite as adsorbents. The calcite was prepared from chicken eggshells by heating and activation methods. It was modified by mixing it with commercial activated carbon as a new adsorbent. XRD and FTIR were used to characterize the adsorbents. Light naphtha fuel from the Al-Diwaniyah refinery, with a sulfur concentration of 776 ppm, was used in batch adsorption studies. Various operation conditions that affect the adsorption process were studied such as temperature (20–40 °C), weight of the adsorbent (1-3 g), and contact time (15–45 min) at constant mixing speed (300 rpm). In this study, the Minitab Program-Box-Behnken design was used to design experiments in batch adsorption studies of light naphtha, which is considered more straightforward and accurate because it shows the effect of each dependent factor on the adsorption efficiency and removal ratio. Results and analysis showed that the increase in temperature, the amount of adsorbent, and contact time would increase the removal efficiency. The analysis of adsorption equilibrium isotherms shows that the experimental data follows the Freundlich isotherm model for adsorbents. According to the results of the study, the highest removal percentages of sulfur content of light naphtha using calcite and modified calcite were 61% and 79%, respectively.